Smart Retailing in COVID-19 World: Insights from Egypt (European Journal of Marketing and Economics, 2020)
COVID-19 pandemic has had a significant impact on business in general and the retail sector in particular which was hardly hit as sales fell by 20 percent during this period. The main challenges that face retailers nowadays during COVID-19 outbreak include: balance in supply and demand; safety of employees; trust between retailer and consumer; distribution - transportation capability; shortage of manpower and consumer behavior (Fernandes, 2020; Kumar et al., 2020; Pantano et al., 2020). Yet, retailers around the world started to understand the benefits and new opportunities offered by smart technologies (Inman and Nikolova, 2017; Renko and Druzijanic, 2014). New technologies like internet of things (IoT) can play a significant role in controlling the pandemic situation in the retail sector and are expected to bring substantial benefits such as lower labor costs, increased efficiency, attraction of new shoppers and the generation of new revenue channels (Roy et al., 2017; Vaishya et al., 2020; Wünderlich et al., 2013). However, only a limited number of retailers has adopted IoT due to the huge financial investments required and uncertainty of customers' acceptance (Alkemade and Suurs, 2012; Evans, 2011; Pantano et al., 2013). It is, thus, expected to see smart retailers taking a series of actions over the short to medium term to conserve cash and structure of their company for post-COVID-19 operations. This research aims to explore the retailers' perceptions towards the adoption of smart retail technologies in Egyptian retailing context throughout conducting a series of semi-structured interviews with mid-to-top level management in different retail organisations and discuss the advantages and challenges expected from smart retail technologies adoption. Moreover, the research explains how smart retail can help overcoming uncertainities and is considered a well managed response strategy by retailers to COVID-19.
Keywords: COVID-19, Egypt, Internet of Things (IoT), Smart Retail, Retail 4.0, Omni-Channel